PENERAPAN MODEL PEMBELAJARAN INQUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS (KBK) SISWA KELAS XI MIA 1 SEMESTER GANJIL MAN 2 MATARAM TAHUN 2017-2018 - Khusnul Khotimah (Indonesian Journal of Teacher Education, 2020)
This research is a classroom action research conducted in two cycles which aims to find out the increase in critical thinking skills of students of class XI MIA 1 MAN 2 Mataram. The subjects in this study were all students of class XI MIA 1 MAN 2 Mataram, totaling 44 people. Data obtained from tests were analyzed using descriptive statistics. The results of this study indicate that the critical thinking skills of 30 students in the first cycle were in the high category with an average score of 70.02, while in the second cycle there were 36 students in the high category, and the average score of 75.6 increased their absorption ability from 68 , 18 percent to 81.8 percent. This study concludes that there is an increase in students' critical thinking skills and student learning outcomes in class XI MIA 1 MAN 2 Mataram through the guided inquiry method.